MongoDB in a Cloud Environment (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
With more and more businesses adopting cloud computing, cloud-based database  adoption is becoming a common practice. A well-liked NoSQL database,  MongoDB is ideal for cloud deployment because of its scalable and adaptable data  storage features. The purpose of this study is to examine the advantages and factors  to be taken into account while implementing MongoDB in a cloud environment.  The cloud environment presents several advantages for MongoDB deployment,  such as high availability, scalability, and integration capabilities. To guarantee a  successful and effective implementation, enterprises must carefully take into  account elements like data security, network connectivity, and cost management.  Organizations may make well-informed decisions and fully utilize MongoDB in  the cloud by being aware of the advantages and factors related to MongoDB hosted  on the cloud.
Keywords: Cloud; MongoDB; Access Control; Security; Database